Feasibility of tomato production in aquaponic system using different substrates (Progressive Agriculture, 2015)
An aquaponics experiment was conducted to test the efficacy of different substrate such as gravel mixed with saw dust (1:1, T1), only brick lets and gravels (T2 and T3) for 116 days from 1 March to 25 June, 2013 at the roof of a building at Bangladesh Agricultural University (BAU) residential area with two replications to produce tomato in summer. Tilapia (mean initial length and weight were 6.18±0.92 cm and 5.85±2.30 g, respectively) used as test animal at the rate of 134 fish/m3 water. The twenty days old healthy tomato seedlings were transplanted to the grow bed after stocking of tilapia. The waste water from the fish tank was irrigated using a 12 watt submersible pump to the vegetable beds and tank water was aerated with a 10 watt air pump fitted with two air stones. The irrigated water passed through the substrate where denitrifying and nitrifying bacteria converted nitrogenous compound to nitrites and then nitrates which then used by tomato plants as fertilizer and filtered water returned to the fish tank. Water quality, plant and fish growth were monitored fortnightly and detailed test was carried out three times in the lab. Evaporated and used up water was replaced with tap water daily. Data analysis showed that the water quality parameters were within the suitable range of fish culture. The mean length and weight of fish increased by 10.42±1.11 cm and 86.26±17.40 g, respectively. The FCR for tilapia feed used in the present aquaponic system was 2.73. Daily growth rate was 0.74% and the survival rate was 90%. Total fish production was found 130 tons/ha/116 days. In case of tomato, the results showed that overall plants growth and weight of fruits was higher in T3 than T1 and T2. Tomato production was 22.25, 37.74 and 87.41 tons/ha/116 days in T1, T2 and T3, respectively. Thus, present results revealed that the gravels substrate gave the highest tomato production than the brick lets and gravels mixed with saw dust substrate.Progress. Agric. 2014. 25: 54-62